Dietary Sodium, Potassium, Magnesium, and Calcium: Effects on Risks of Incident Cardiovascular Disease in the Framingham Offspring Study. (29th May 2020) - Pickering, R Taylor; Bradlee, M Loring; Singer, Martha; Moore, Lynn l
Abstract: Objectives: The objectives of this study were to determine the dose-response relations and combined effects of sodium, potassium, magnesium and calcium on the risk of cardiovascular disease. Methods: Data for 2362 30–64 year-old men and women free of CVD at baseline in the Framingham Offspring Study were included in these analyses. Cox proportional hazard models were used to investigate the association between categories of sodium, potassium, calcium, and magnesium intake and risk of incident CVD. Further, Cox models with restricted cubic spline functions were used to examine the dose-response relations of these minerals with CVD risk. Results: Compared with higher sodium intakes (≥3500 mg), those with the lowest intakes (<2500 mg/d) had no statistically significant reduction in risk of CVD. In contrast, potassium intake ≥3000 (vs. <2500) mg/day was associated with a 25% lower risk (95% CI: 0.59–0.95) of CVD; magnesium intake ≥320 (vs. <240) mg/day led to a 34% lower risk (95% 0.51–0.87). Restricted cubic spline curves showed inverse dose-response relationships for both potassium and magnesium with CVD risk but no association with either sodium or calcium. Higher intakes of both potassium and magnesium were beneficially associated with CVD risk even among those with sodium intakes ≥2500 mg/day. Conclusions: Sodium intake was not associated with CVD risk within the range of intakes generally consumed by these participants. In contrast, higher intakes of both potassium and magnesium were inversely associated with risk of CVD. Funding Sources: Funding for this work was provided by the National Heart Lung and Blood Institute and National Dairy Council.